Association between depressed mood and sexual function among mid-aged Paraguayan women. (1st November 2020) - Sánchez-Zarza, S. C.; Mezones-Holguín, E.; López-Baena, M. T.; Soto-Becerra, P.; Pérez-López, F. R.; Gavilanes, A. W. D.; Chedraui, P.
Abstract: Background: Depressive symptoms may affect female mid-life sexuality, whereas sexual problems tend to aggravate depression. Despite this, data assessing this association drawn from mid-aged Paraguayan women are scarce. Objective: This study aimed to assess the association between depressed mood and the risk of sexual dysfunction during female mid-life. Methods: Sexually active urban-living women from Asunción, Paraguay ( n = 193, aged 40–60 years) were surveyed with the 6-item Female Sexual Function Index (FSFI-6), the 10-item Center for Epidemiological Studies Depression Scale (CESD-10), and a general questionnaire containing personal and partner information. Depressed mood was defined as a total CESD-10 score of 10 or more, and an increased risk for sexual dysfunction as an FSFI-6 total score of 19 or less. The association of depressed mood and an increased risk of sexual dysfunction was evaluated with multivariable Poisson regression. Results: The mean age (±standard deviation) of surveyed woman was 48.3 ± 6.0 years and 61.1% ( n = 118) were perimenopausal and postmenopausal. A total of 21.8% ( n = 42) had depressed mood and 28.5% ( n = 55) had an increased risk of sexual dysfunction. The final adjusted regression model determined that women with depressed mood were twice as likely to have an increased risk of sexual dysfunction, compared to women with normal mood (adjusted prevalence ratio = 2.14, 95% confidence interval 1.26–3.60). On the other hand, depressed mood was associated with a mean total FSFI-6 score that was 20% lower than that observed among women with normal mood (adjusted incidence rate ratio = 0.80, 95% confidence interval 0.68–0.93). Conclusion: In this mid-aged Paraguayan female sample there was a significant association between depressed mood and an increased risk of sexual dysfunction.